THE IMPORTANCE OF LAND REGISTRATION DETAILS (SKPT) IN AUCTION PROCESS OF EMPLOYEE RIGHTS - Putri, Megawati Nur (Universitas Tadulako, 2019)
The auction is a sale of general public goods by an oral and / or written bid that increases or decreases to achieve the highest price, preceded by the effort of collecting prospective buyers/auctions led by auction officials. The transfer of rights through auction can only be registered if it is proved by auction quotation quotes made by the auction official and at the auction of the object of mortgage, it is very necessary a certificate issued by the National Land Agency (BPN) in which the auction object is based on a written request from the Head of the Auction Office. The certificate in question is the Land Registration Certificate (SKPT). Land Registration Certificate is very important in the auction process of Mortgage Rights because it is a much needed requirement. In the certificate of registration the land explains the physical data and juridical data as well as the identity of the object of Mortgage Rights that will be in the auction and also to know the last condition of the status of the land. Function of Land Registration Certificate as the latest source of information on the right to land or Property Owned Up Unit Flats to be auctioned. Auction conducted without a Certificate of Land Registration then the auction is invalid and legally flawed, and the result is null and void. Because auction officials are prohibited from auctioning the object of Mortgage Rights if not equipped with Land Registration Certificate (SKPT).Â